Optimalisasi Destilasi Nilam Kering melalui Pembekuan Pra Destilasi - Sugiarto, Sugiarto; Sutikno, Djoko; Widhiyanuriyawan, Denny; Sonief, A. Asâ€™ad (Rekayasa Mesin, 2014)
The process of extracting oil from the leaves or stems cells by damaging the cell which usually done before or during distillation process. Damaging the cell can be done by mechanical process or freezing process. Chopping the leaves was done to damage the cells through the mechanical process, however the damage have not been able to destroy up to the celular level. While the freezing process could be expected to damage the tissue at the cellular level. Pure research on laboratory scale was used as the experiment method in this study. Freezing temperature pasca-distillation was variated on -13,4 ÂºC, -19,6 ÂºC and -24,8 ÂºC and without freezing process. While distillation process was varied on 95 ÂºC, 105 ÂºC dan 115 ÂºC. In this study, patchouli was distilled on wet and dry condition. LPG was used with automatically combustion control system of for keeping the temperature stability, increasing the capacity and quality of patchouli oil and reducing the production cost and the distillation time to less than 6 hours The stable distillation temperature was able to raise the volume of oil per kilogram of dry weight raw material and decrease the distillation time to less than 5 hours. Patchouli oil volume produced per kilogram of dry raw materials post freeze predistillation increased with increasing the distillation temperature. The low freezing temperature of the pre-distillation produced the high volume of patchouli oil per kilogram of raw material. Pre-distillation on the freezing process of dried patchouli was able to shorten the time of maximum distillation only in 3 hours. The range of distillation temperature on 95 â°C, 105 â°C and 115 â°C produced the different colors of patchouli oil from light brown to dark brown color.Keywords : optimalisation, distillation, dry patchouli, freeze pre-distillation